The 'Social Life' of Conservation: Lessons from Danau Sentarum - Wadley, R.L.; Colfer, C.J.P.; Dennis, R.A.; Aglionby, J. (2010)
This article focuses on a team’s collaborative conservation experience, beginning in 1991 in Danau Sentarum National Park in West Kalimantan, Indonesia. The experience of three teams is recounted as they worked collaboratively with local Malay and Iban communities to manage the flooded and lowland tropical forest area. Relations between conservation workers and communities are discussed, and social capital among conservation workers is highlighted as another centrally important feature in conservation success. Subsequent involvement of the network of concerned researchers is also described. Central points of the article are 1) that conservation practices are socially embedded, and 2) that a “best practices” approach is inadequate when personal characteristics, experiences, and networks have such long lasting impacts on conservation itself.